Participatory Cartography as a Didactic Strategy in the Teaching of Citizenship Education - Zúñiga Villalobos, Dylan (2023)
This article analyzes the use of participatory cartography as a didactic strategy in the teaching of citizenship training. To achieve this, it uses theories of situated cognition and didactics of Geography for citizen participation to territorialize the perceptions of citizen security of the Hatillo district, San José, Costa Rica. The research uses the development of critical collective mapping workshops as a form of participatory intervention of the practice with classroom actors. The evaluation of the strategy conducted by the participating teacher is addressed together with the systematic assessment of the experience with the students. The findings of this work allowed the construction of a heat map that positions the subjective zoning for the risk management of the students in situations of insecurity, as a geodidactic innovation for citizen training in the subject of Civic Education.